2021
DOI: 10.3390/jcm10091829
|View full text |Cite
|
Sign up to set email alerts
|

Hyperuricemia as a Marker of Reduced Left Ventricular Ejection Fraction in Patients with Atrial Fibrillation: Results of the POL-AF Registry Study

Abstract: Background: Hyperuricemia is an established risk factor for cardiovascular disease, including atrial fibrillation (AF). The prevalence of hyperuricemia and its clinical significance in patients with already diagnosed AF remain unexplored. Methods: The Polish Atrial Fibrillation (POL-AF) registry includes consecutive patients with AF hospitalized in 10 Polish cardiology centers from January to December 2019. This analysis included patients in whom serum uric acid (SUA) was measured. Results: From 3999 POL-AF pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 28 publications
2
8
0
Order By: Relevance
“…It is also regarded as a risk factor closely correlated with hypertension, type 2 diabetes mellitus, and hyperlipidemia [ 2 , 3 ]. Previous reports have suggested that hyperuricemia is tangled with the injuries to the intestinal tract [ 4 ], liver [ 5 ] and heart failure [ 6 ]. Hyperuricemia and associated disorders cause a significant economic burden on modern society.…”
Section: Introductionmentioning
confidence: 99%
“…It is also regarded as a risk factor closely correlated with hypertension, type 2 diabetes mellitus, and hyperlipidemia [ 2 , 3 ]. Previous reports have suggested that hyperuricemia is tangled with the injuries to the intestinal tract [ 4 ], liver [ 5 ] and heart failure [ 6 ]. Hyperuricemia and associated disorders cause a significant economic burden on modern society.…”
Section: Introductionmentioning
confidence: 99%
“…Elevated SUA has been shown to inhibit nitric oxide production by vascular endothelial cells and also to inhibit their proliferation and migration [ 15 ]. In the clinical trial, there are several observational studies and meta-analyses that described elevations of SUA as an independent marker of poor cardiac function, mortality, and poor exercise capacity [ 16 18 ]. Increased SUA levels might lead to the echocardiographic abnormalities through impacts on endothelial function and inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in the presented study, AF type or impaired kidney function were not shown to be the predictors of OAC use in patients at low thromboembolic risk. It has been reported that the aforementioned factors increase the risk of thromboembolic complications in patients with AF or predispose them to thrombus formation in the left atrial appendage [8][9][10][11][12][13][14][15][16][17][18][19][20]. Study results connected with anticoagulant overtreatment of patients with AF prove that it is common and most likely stems from using OACs due to temporary indications to anticoagulant therapy and from the presence of thromboembolic risk factors not included in the CHA 2 DS 2 -VASc score.…”
Section: Discussionmentioning
confidence: 99%
“…The POL-AF Registry (NCT04419012) was a prospective, observational study enrolling AF patients hospitalized in 10 cardiology departments in Poland (eight of them were academic and two regional). Details on the study design have been reported elsewhere [9][10][11]. In brief, consecutive hospitalized patients were included in the study on the condition that they were at least 18 years of age and had AF history reported by electrocardiography or in their case record.…”
Section: Study Populationmentioning
confidence: 99%